An Ethics Toolkit to Support Animal-Centered Research and Design - Ruge, Luisa; Mancini, Clara (Frontiers in Veterinary Science, 2022)
Designers and researchers who work with animals need to employ an array of ethical competencies to guarantee the welfare and wellbeing of animals taking part in animal-centered research. The emerging field of Animal-Computer Interaction (ACI), which deals with the design of animal-centered interactive systems, considers ethics a fundamental concern when working with animals and ACI researchers have proposed ethics frameworks in response to these concerns. However, ethical approaches proposed within the field tend to be normative, which limits the support they can provide for designers who will inevitably face unexpected and ethically charged situations. During a research project, focused on the design of dog-friendly controls for Mobility Assistance Dogs (MADs), these limitations came to the fore. Drawing from situated ethics approaches, developed to support researchers’ ethical engagement with vulnerable populations such as children and differently-abled adults, this paper presents an ethics toolkit that aims to support animal-centered research and design by enabling researchers to make ethically sound situated decisions as their work progresses. The toolkit comprises three templates, each of which asks a series of questions aiming to articulate the ethical baselines of individual team members and of their research project and to inform the development of a series of ethical guiding statements to better prepare designers to make ethical situated ethical decisions. The application of the toolkit during the research with MADs helped the field researcher to clearly and systematically articulate the project’s ethos, understood as the ethical stance that guided the research team’s interactions with the dogs, their trainers, and their human partners throughout the project. It also fostered a practice of active reflection within the team, which helped them to maintain their commitment to the project’s ethos in the face of unexpected ethical challenges. We propose that, beyond supporting ACI research, the toolkit could support the ethical engagement of researchers and practitioners who work for and with animals in many other settings.